Civil engineering and environmental systems (Taylor & Francis Group, 2009)
Civil Engineering and Environmental Systems is devoted to the discussion, dissemination and development of systems techniques and their underlying assumptions through the spectrum of civil engineering activity and environmental decision-making and management.